2015
DOI: 10.7897/2230-8407.06236
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Antioxidant Activity of Spondias Mombin Leaf Extract: Discovering Future Avenues for an Affordable and Efficient Antioxidant

Abstract: Spondias mombin is valued ethno medically in folkloric medicine. This medicinal plant according to traditional claim is said to cure various infectious and inflammatory ailments of gastrointestinal and genitourinary tract. Formation of reactive oxygen species (ROS) in inflammatory conditions is said to result in oxidative stress. The antibacterial and anti-inflammatory properties of Spondias mombin especially its leaves, have been linked to a range of compounds in it viz., anthraquinones, berberine, flavonoids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The activity of compound 9 (IC50 = 11.8 μg/mL) was similar to that of the regular drug, ascorbic acid (IC50 = 9.4 μg/mL). This is in agreement with a study carried out 28 using the ethanol leaf extract of S. mombin, where the DPPH scavenging property was comparable with the regular drugascorbic acid. A positive result was also observed for the extracts/fractions of the leaf of S. mombin using in vitro DPPH scavenging assay.…”
Section: Dpph Free Radical Scavenging Activitysupporting
confidence: 92%
“…The activity of compound 9 (IC50 = 11.8 μg/mL) was similar to that of the regular drug, ascorbic acid (IC50 = 9.4 μg/mL). This is in agreement with a study carried out 28 using the ethanol leaf extract of S. mombin, where the DPPH scavenging property was comparable with the regular drugascorbic acid. A positive result was also observed for the extracts/fractions of the leaf of S. mombin using in vitro DPPH scavenging assay.…”
Section: Dpph Free Radical Scavenging Activitysupporting
confidence: 92%
“…Rice-Evans [ 51 ] reported that compounds with phenolic content could play an important role in eliminating radicals. The ABTS∙ scavenging property of the leaf might be due to the donating ability of the phenolics present in the fractions [ 52 , 53 , 54 ]. The antioxidant capacity of the leaves can be linked to their bioactive compounds, mainly antioxidant polyphenols, because of their ability to scavenge free radicals [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might be connected to how diverse the extracts from various solvents' secondary chemical profiles are characterized [36]. Accordingly, similar investigations conducted in the past [37,38] have demonstrated that extracting S. mombin with polar solvents improved its antioxidant capabilities when compared with reference antioxidant compounds.…”
Section: Effects Of Various Solvent Extracts Of S Mombin Leaves On Dp...mentioning
confidence: 84%